2016
DOI: 10.1021/acsnano.6b05502
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Iron-Loaded Synthetic Melanin

Abstract: We describe a synthetic method for increasing and controlling the iron loading of synthetic melanin nanoparticles and use the resulting materials to perform a systematic quantitative investigation on their structure–property relationship. A comprehensive analysis by magnetometry, electron paramagnetic resonance, and nuclear magnetic relaxation dispersion reveals the complexities of their magnetic behavior and how these intraparticle magnetic interactions manifest in useful material properties such as their per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
139
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(147 citation statements)
references
References 54 publications
2
139
2
1
Order By: Relevance
“…In a typical synthesis, approximately 50 mg products could be obtained, determined by weighing after lyophilization. The Mn loading efficiency reached 10.2% wt/wt (Table S1, Supporting Information), which is much higher than previous studies 13, 29, 32, 33. It suggests more efficient synthesis and higher yields than conventional PPD approaches.…”
mentioning
confidence: 68%
“…In a typical synthesis, approximately 50 mg products could be obtained, determined by weighing after lyophilization. The Mn loading efficiency reached 10.2% wt/wt (Table S1, Supporting Information), which is much higher than previous studies 13, 29, 32, 33. It suggests more efficient synthesis and higher yields than conventional PPD approaches.…”
mentioning
confidence: 68%
“…In our previous work, it was shown that increasing Fe(III) ion concentration within polydopamine nanoparticles led to antiferromagnetic coupling that correlated with decreases in MR contrast. To investigate whether Gd(III)–Gd(III) coupling or the formation of Gd oxide phases at high concentrations could be playing a role in the decrease in r 1 , the magnetic properties of GdPD‐NPs were investigated by variable‐temperature magnetic susceptibility measurements from 2 to 300 K under a 5000 Oe magnetic field (Figure S9, Supporting Information).…”
Section: Selected Relaxation Parameters Obtained From the Analysis Ofmentioning
confidence: 92%
“…In our previous study describing tunable Fe(III) loadings in PD‐NPs via the prepolymerization chelation strategy, we found that antiferromagnetic coupling between Fe(III) centers lowered their r 1 as we increased Fe(III) loadings in the particles . We hypothesized that Gd(III) would exhibit much less antiferromagnetic coupling because of the poor radial extension of the f‐orbitals.…”
Section: Selected Relaxation Parameters Obtained From the Analysis Ofmentioning
confidence: 96%
“…Additionally, by coating iron oxide (Fe 3 O 4 ) surfaces with PDA, or the absorption of metal ions (i.e., Fe 3+ , Fe 2+ , Gd 3+ and Mn 2+ ) into PDA NPs, PDA can be used for magnetic resonance imaging. Li et al employed electron paramagnetic resonance, magnetometry, and nuclear magnetic relaxation dispersion to characterise PDA NPs loaded with iron [89]. The results indicated the presence of isolated iron centres with paramagnetic properties within the NPs, resulting in the measured magnetic resonance imaging signals [89].…”
Section: Biomedical Applications Of Pda Coatingsmentioning
confidence: 99%
“…Li et al employed electron paramagnetic resonance, magnetometry, and nuclear magnetic relaxation dispersion to characterise PDA NPs loaded with iron [89]. The results indicated the presence of isolated iron centres with paramagnetic properties within the NPs, resulting in the measured magnetic resonance imaging signals [89]. Similarly, magnetic NPs were coated with PDA as described by Mrowczynski et al [90].…”
Section: Biomedical Applications Of Pda Coatingsmentioning
confidence: 99%